Amanhã, a geografia social? - Julien Aldhuy; Fabrice Ripoll; Raymonde Séchet; Vincent Veschambre (Confins)
The purpose of this article is to share theoretical ideas underway in the social geography and more broadly to examine the role of geography in the social sciences. Two major tendencies can be distinguished, related to the major theoretical tasks in social geography, both relevant across the discipline. First, it has been deemed necessary to include geography in a mode of critical knowledge able to integrate the values of empowerment and justice in the development of the knowledge produced. In a second step we highlight the contribution of geography to the social inclusion of the discipline in the social sciences. Confirming this, we claim simultaneously the importance and pervasiveness of space and engage in a dimensional approach to space beyond the contradiction of a science that would be social while taking up space intended, in order to assert its autonomy. This requires a deconstruction of spatial categories in force within the discipline and the adoption of concepts that refer to the spatial dimension of social relations.